The Use of Pictorial Word Dice Media as an Alternative Learning Media for Beginning Reading of 2nd Grade of Elementary School. - Analaris, Yasinta; Widjojoko, Widjojoko; Wardana, Deni (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Pictorial word dice is basically a dice where each side is pinned with words and pictures for students to read. Used of pictorial word dice media will be explained in the form of learning plans or commonly referred to as lesson plans. This lesson plan mainly pays attention to learning themes, basic competencies and indicators of learning Indonesian in the second grade of elementary school. This study using a descriptive method with data processing techniques literature study. The description is of course based on a literature review that was developed through the author's interpretation in a scientific, concise, and clear manner. The sources of data obtained from previous research, books and journals that are relevant to this research. The first result of this study is to provide a general and comprehensive description of the characteristics of the pictorial word dice media that can be used as a medium for learning to read beginning. Second, it provides a description of the initial reading lesson plan associated with the use of pictorial word dice media, namely in the form of a plan for implementing Indonesian language learning activities for early reading in the second grade of elementary school. This literature study can be used as a basic basis for developing learning using picture dice in further research.